Alterations in lymphocyte, neutrophil and eosinophil count under stress of nickel nitrate in albino rat - REENA YADAV; P.K. SINGH; NEELAM UPADHYAY (International Journal of Pharma and Bio Sciences, 2019)
Metals are used in industry, agriculture and medicine and can exert occupational or homicidal toxicity. They interfere with the function of essential cations and cause enzyme inhibition to generate oxidative stress. As a result, multisystem signs and symptoms are a hallmark of heavy metal intoxication. In case of intoxication, chelators may be used to bind the metal and facilitate its excretion from the body. Nickel exists in our surroundings in the form of packaging, contamination, industrialization etc. It has so heavily contaminated the surrounding that exposure to it is unavoidable. This study was aimed at evaluate the possible effects of nickel nitrate exposure on blood parameters targeting to lymphocytes, neutrophils and eosinophils. Predetermined doses of nickel nitrate (Ni(NO3)2] in acute (1 day) and subacute (7, 14, 21, 28days) treatments revealed significant alterations in lymphocytes, neutrophils and eosinophils. The results indicate extent of toxicity and alterations in lymphocytes, neutrophils and eosinophils under toxic stress of nickel nitrate in albino rat. This study will imply new dimensions in heavy metal research. The study directly related to humans as albino rat are very similar to human in physiological and biochemical aspects. Further, modernization of our life with daily increase in digitalized equipment’s increase the risk to exposure with heavy metals.